HIGH ALTITUDES EFFECTS ON HEMATOLOGIC BLOOD PARAMETERS - Hasim Rushiti; Florian Miftari; Besim Halilaj (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2015)
The approach and the objective of this experiment are consistent with the determination of changes of blood parameters after the stay of the students at an altitude of 1800-2300 meters, for a ten-day long ski course. In this paper are included a total of 64 students of the Faculty of Sport Sciences in Prishtina, of the age group of 19-25 (the average age is 21). All students previously have undergone a medical check for TA, arterial pulse and respiratory rate. In particular, the health situation is of subjects was examined, then, all students, at the same time, gave blood for analysis. In this experiment, three main hematologic parameters were taken in consideration: such as hemoglobin, hematocrit and red blood cells. The same analyses were carried out after the 10-day stay at a high altitude. The results of the experiment have shown significant changes after the ten-day stay at high altitude, despite the previous results that show changes only after the twenty-day stay in such elevations.